Pembuatan Na2O/Fly Ash sebagai Katalis Pada Proses Transesterifikasi Minyak Sawit Off Grade Menjadi Biodiesel - Surya, Andry Pratama; Helwani, Zuchra; Saputra, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
A fly ash supported sodium oxide (Na2O) catalyst used in transesterification reaction of off-grade palm oil for biodiesel production. The catalyst synthesized by loading Na2O from sodium nitrate (NaNO3) into fly ash micro pore through impregnation method. The optimum catalyst preparation conditions were determined by influence of calcination temperature and weight ratio of NaNO3/fly ash. Catalyst with highest catalytic activity was achieved when calcined at 550oC and proportion of NaNO3/fly ash is 90:10. Under the conditions of oil : methanol ratio of 1:8, catalyst dosage of 4 wt% and temperature of 60oC for 3 h, the biodiesel yield reaches to 89,12%. Na2O, SiO2, NaNO3 and Na2O2 were found in the catalyst through X-ray diffraction (XRD) while the basic strength of the catalyst H_ > 9,3 was determined by using Hammett indicator phenolphthalein. Surface area of the developed catalyst is 21,651 m2/g through Brunauer-Emmett-Teller (BET). Characteristics of biodiesel such as density, kinematic viscosity, acid value, flash point has been matched with standard for biodiesel specification of Indonesia.Keywords: biodiesel, sodium oxide, catalyst, fly ash, impregnation, calcination, transesterification.